Cooperative advertising and pricing in an O2O supply chain with buy‐online‐and‐pick‐up‐in‐store. (4th May 2020) - Li, Mengli; Zhang, Xumei; Dan, Bin
Abstract: This paper investigates the effectiveness of cooperative advertising in an online‐to‐offline (O2O) supply chain where the manufacturer cooperates with the retailer to implement buy‐online‐and‐pick‐up‐in‐store (BOPS) strategy. Considering the coexistence of channel cooperation and channel competition after the implementation of BOPS, we investigate the impact of BOPS on equilibrium results. Then we study the optimal cooperative advertising and pricing strategy of the O2O supply chain. We also identify the effectiveness of cooperative advertising on the O2O supply chain and supply chain members. We find that the implementation of BOPS can partially substitute the incentive effect of cooperative advertising. In addition, convenience coefficient and commission rate, the two key factors of BOPS, have opposite impacts on optimal decisions in most conditions. Therefore, the optimal strategy depends on the balance of the above two factors. Furthermore, we find that cooperative advertising does not always benefit the O2O supply chain and its members.